2018
DOI: 10.1113/jp275776
|View full text |Cite
|
Sign up to set email alerts
|

Saving the brain one heartbeat at a time

Abstract: In an article in this issue of The Journal of Physiology, Yamaguchi et al. (2018) set out to demonstrate the time course of changes in several widely used heart rate variability (HRV) measures during an exposure to a hypoxic-ischaemic (HI) insult using fetal sheep as a model.Although this study was conducted in a fetal model, the findings may well be useful as a surrogate for the neonate with HI encephalopathy that needs timely diagnosis for effective treatment. This information is difficult to obtain from ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 6 publications
3
27
0
Order By: Relevance
“…Finally, Van Laar et al found a rise in LF and a decrease in HF HRV in the last 30 minutes of labor when pH was <7.05 at birth . However, commonly used HRV analysis methods have significant interindividual variability and require post‐treatment, which precludes their use in current practice …”
Section: Discussionmentioning
confidence: 99%
“…Finally, Van Laar et al found a rise in LF and a decrease in HF HRV in the last 30 minutes of labor when pH was <7.05 at birth . However, commonly used HRV analysis methods have significant interindividual variability and require post‐treatment, which precludes their use in current practice …”
Section: Discussionmentioning
confidence: 99%
“…Our present work highlights the difficulty in summarizing fHRV changes as being more/less complex or suppressed/increased variability. (Frasch, 2018) The various HRV measures characterize different, sometimes conflicting, aspects of the signal and the dynamics of the underlying system. It is for this reason that we introduced the terms "HRV code" and "vagus code".…”
Section: Discussionmentioning
confidence: 99%
“…We invite the interested reader to explore this study and test the identified measurable d) The HRV code has been proposed as an overarching concept incorporating the various multi-scale contributions of inter-organ communication reflected in HRV. [8,46,47] We suggest that an understanding of the impact on CPS of chronic fetal hypoxia or infection during pregnancy should be sought within the integrative framework of the HRV code; e) Could we use mathematical modeling to derive predictions for HRV properties, likely to work as iHRV biomarkers in the human clinical setting? Mathematical models exist for CPS and fetal cardiovascular responses to labor, for example.…”
Section: ) Can the Impact Of Fetal Hypoxia Or Infection On Cps Be Camentioning
confidence: 99%
“…[6] The analysis of fetal heart rate variability (HRV) has been the mainstay of noninvasive fetal health monitoring for decades, yet its utility to identify endangered fetuses has remained limited. [7,8] In this review, we will discuss how the CPS provides the subcellular, cellular and multicellular substrate for the emergence of an intrinsic fetal HRV (iHRV). We hope that expanding research into the iHRV as a proxy to fetal cardiac health will not only help in the diagnosis of fetuses at risk in adverse pregnancy, but that it will also inspire future studies into this aspect of cardiac cellular development and its significance for the early detection of cardiac diseases in later life.…”
Section: Introductionmentioning
confidence: 99%